Changing trend in the management of omphalocoele in a tertiary hospital of a middle-income country - Olakayode Olaolu Ogundoyin; Akinlabi Emmanuel Ajao (Wolters Kluwer Medknow Publications, 2021)
Background: The peri-operative management of omphalocoele in low- and middle-income countries is challenging owing to non-availability of neonatal intensive care units and equipment needed for the care of this anomaly. Aim: This study examined our experience in the management of omphalocoele and compared the pattern and outcome with a similar study from the same centre conducted four decades ago. Methods: A retrospective study of neonates managed for omphalocoele from 2003 to 2017 (Group A) was performed. Their demographic characteristics, clinical presentation, management modality and outcome were obtained and statistical analysis was performed to determine the predictors of mortality. The findings were also compared with the findings of a similar study (Group B) published from this centre four decades ago from 1973 to 1978. Results: A total of 95 patients were managed in Group A and 33 in Group B. Their ages ranged from 1 to 15 days with a median age of 1 day and a median gestational age at birth of 37 weeks (range - 36-43 weeks) in Group A and 5-72 h in Group B. There were 54 (56.8%) boys and 41 (43.2%) girls in Group A and 17 (51.5%) boys and 16 (48.5%) girls in Group B. Rupture of the sac was observed in 18 (18.9%) patients in Group A and 13 (39.4%) in Group B. Operative management was adopted for 55 (57.9%) patients in Group A compared to 14 (42.4%) in Group B. Mortality was recorded in 16 (16.8%) patients in Group A and 16 (48.5%) in Group B. Following further analysis in Group A, management outcome was noted to be significantly associated with the state of the sac (P = 0.011), presence of associated sepsis (P = 0.002) at presentation and management modality (P = 0.048) with only associated sepsis independently predicting mortality. Conclusion: Although epidemiological trend and clinical presentation are still similar, management outcome has improved over the years.